If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 = -2a + 7(5 + -7a) -16 = -2a + (5 * 7 + -7a * 7) -16 = -2a + (35 + -49a) Reorder the terms: -16 = 35 + -2a + -49a Combine like terms: -2a + -49a = -51a -16 = 35 + -51a Solving -16 = 35 + -51a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '51a' to each side of the equation. -16 + 51a = 35 + -51a + 51a Combine like terms: -51a + 51a = 0 -16 + 51a = 35 + 0 -16 + 51a = 35 Add '16' to each side of the equation. -16 + 16 + 51a = 35 + 16 Combine like terms: -16 + 16 = 0 0 + 51a = 35 + 16 51a = 35 + 16 Combine like terms: 35 + 16 = 51 51a = 51 Divide each side by '51'. a = 1 Simplifying a = 1
| 6x-10=68 | | -77=7(-8x-3) | | y-4(2)=0 | | 8=-4(-8n-2) | | -3(-8-6b)=6 | | 61=-5(1-8v)-7v | | -6=-6(-7-8n) | | -60=3(-7x+8) | | 7(3r+6)=21 | | 60=6(6m-7)-6 | | -4(3n-4)=-56 | | -25=-1-6(1+3x) | | k^3=144k | | -7(1+3p)=-70 | | 10x^2+40x+2=0 | | 8x^3+64=0 | | 3(2n+4)+5(3-2n)=7-2n | | -2=-7(4a+7) | | 3(2+5x)=-39 | | 6(8k+8)=0 | | 3-4x=0 | | y-4(3)=0 | | -3x+6=2 | | 64y^2+112y+49=0 | | -6=29x | | 4+7z=3z-20 | | y-3(3)=0 | | 4+7z=20-3z | | 2l+2w=264 | | 4v-5=17 | | 2l+2w=264(10w) | | (4x+8)(3x-2)=0 |